FACTORS AFFECTING STUDENTS' RELUCTANCE TO SPEAK ENGLISH IN CLASSROOM INTERACTIONS - Giantari, Khinanti; Kurniawan, Eri; Suherdi, Didi (Universitas PGRI Sumatera Barat, 2023)
EFL students have a big problem called reluctance. Reluctance is students’ unwillingness or disinclination to speak and participate in classroom activities. This research attempts to determine how much each of the three factors affects students’ reluctance to speak English in classroom interactions and which is the most dominant. A descriptive quantitative method was used in this research. A questionnaire was used to collect data. This research analysed the data using version 25 of the Statistical Package for Social Sciences, abbreviated as the SPSS program. The result showed that the weighted average of the proportions of the three factors was 2.66, 2.58, and 2.39, respectively, for psychological, language-related, and socio-cultural factors. It can be concluded that the psychological factor (lack of motivation) was the main factor that affected students’ reluctance to speak in English. Because of that, the students should maintain their high motivation to improve their speaking ability. Additionally, teachers should employ various strategies to create an engaging learning or activity environment that can motivate students.